2016
DOI: 10.14324/000.rp.1485668
|View full text |Cite
|
Sign up to set email alerts
|

Life Study Scientific Protocol

Abstract: ForwardThe Life Study protocol was developed by the scientific leadership team together with experts from a wide range of disciplines drawn from the biomedical, clinical and social science research communities who formed part of a wider affiliated scientific network. The protocol sets out the key research themes of the study, chosen to capitalise on the unique opportunities afforded by the Study design, and to enable a wide range of research questions and policy issues relevant to children to be explored.The L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A detailed description of the protocols for both components, including power calculations and sampling strategies, is given elsewhere (Dezateux et al, 2016b). Full documentation of the study questionnaires and materials can be found at https://www.lifestudy.ac.uk/resources, and these will be useful for readers who wish to gain a deeper understanding of the overall rationale and content of the study.…”
Section: /11/17mentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the protocols for both components, including power calculations and sampling strategies, is given elsewhere (Dezateux et al, 2016b). Full documentation of the study questionnaires and materials can be found at https://www.lifestudy.ac.uk/resources, and these will be useful for readers who wish to gain a deeper understanding of the overall rationale and content of the study.…”
Section: /11/17mentioning
confidence: 99%
“…This sampling design was substantially the one recommended in two reports to the principal funder (Bynner et al, 2007(Bynner et al, , 2009, as set out in the protocol approved by the principal funder following a competitive process, international peer review and assessment by an independent international scientific panel (Dezateux, 2016b). The sampling design was subsequently discussed and refined by a methodology advisory group set up by and reporting to the Life Study Scientific Steering Committee.…”
Section: Introductionmentioning
confidence: 99%
“…'Life Study' comprised an innovative design of two integrated samples -a 'Pregnancy Component', purposively sampled from a small number of areas, and a nationally representative 'Birth Component', with multiple respondents and contacts in each (Dezateux, Knowles, et al, 2016;Goldstein, Sera, Elias, & Dezateux, 2017) (Table 1). Questionnaires were developed with input from clinicians, population, social and biomedical scientists, relevant stakeholders and experts, and in consultation with UK research and policy communities.…”
Section: Introductionmentioning
confidence: 99%